KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 10 TAMBUSAI UTARA KABUPATEN ROKAN HULU - Helly Nur Winarsih; Dudung Burhaudin; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study investigates the possibility to write a text description of students of class VII of SMP Negeri 10 Tambusai Utara Rokan Hulu District. The aim of this study is to describe how high the ability to write text description of class VII students of SMP Negeri 10 and to describe the differences in the ability to write text description between groups or between classes. This study has a population of 55 and 48 samples. The result of this study is the possibility to make the description text equal to the comparison value. The comparative score used in this study was 69. The students' ability to write was the same as the comparative score, which meant that the ability to write class VII course text was moderate. In other words, the hypothesis is accepted. Then tested using Mann Whitney Test. The result is that there is a difference in the ability to write a text description of class VII students between classes.Key words: ability, writing, description text, student